2020
DOI: 10.1063/1.5124548
|View full text |Cite
|
Sign up to set email alerts
|

XRISE-M: X-radiography facility for solidification and diffusion studies of alloys aboard sounding rockets

Abstract: A compact fully-protected micro-focus X-radiography facility (XRISE-M) is presented for the study of microstructure evolution during solidification of thin liquid alloy samples and chemical diffusion in liquid binary alloys in-situ and in real-time aboard a sounding rocket. XRISE-M presently enables the simultaneous processing of either two near-isothermal solidification furnaces or a combination of a linear-shear cell diffusion furnace and a near-isothermal solidification furnace. For optimal detector calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…1(a) and (b) for the Al-Cu and the Al-Ge alloy, respectively. While the Al 15 wt.%Cu sample was processed in microgravity condition on the sounding rocket flight MAPHEUS-7 in the module X-RISE-M [34], the Al-29 wt.%Ge alloy was processed horizontally on ground in the facility X-RISE-G [35]. In order to investigate the orientation of the dendrites in three dimensions, X-ray computed tomography was performed on the solid samples post-mortem with a Phoenix Nanotom 160NF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1(a) and (b) for the Al-Cu and the Al-Ge alloy, respectively. While the Al 15 wt.%Cu sample was processed in microgravity condition on the sounding rocket flight MAPHEUS-7 in the module X-RISE-M [34], the Al-29 wt.%Ge alloy was processed horizontally on ground in the facility X-RISE-G [35]. In order to investigate the orientation of the dendrites in three dimensions, X-ray computed tomography was performed on the solid samples post-mortem with a Phoenix Nanotom 160NF.…”
mentioning
confidence: 99%
“…It can therefore not be conclusively clarified whether nucleation of Al-grains at the sample boundary favors a special orientation. A more accurate statement could be made with a higher number of grains sampled, but this is difficult because opportunities for experiments in microgravity are rare [34,38]. What can be stated, however, is that the crystallographic {100} plane of most grains nucleated in microgravity is not parallel to the sample plane in the solidified samples, as one might assume by looking only at the projected dendrite morphologies, which in many cases show a four-fold symmetry (see Fig.…”
mentioning
confidence: 99%
“…Additional near-isothermal solidification experiments have been carried out on two sounding rocket missions MAPHEUS-6 and 7 in the years 2016 and 2018, respectively, also using X-ray observation technology and a different isothermal furnace design 23 . Two Al-15 wt.% Cu samples in two individual solidification furnaces sharing one X-ray source have been solidified in microgravity during MAPHEUS-7, and one Al-46wt.% Ge sample during MAPHEUS-6 24 . Nucleation dynamics as well as dendrite and melt concentration evolution were monitored in-situ.…”
Section: Equiaxed Solidificationmentioning
confidence: 99%
“…However, X-ray radioscopy is essential to monitor the diffusion process and rule out disturbing effects. For selected binary alloys sounding rocket (MAPHEUS) experiments using the XRISE-M facility 24 were compared with ground-based experiments 54 , 55 . It was shown that diffusion experiments can be successfully carried out on ground, if a stable density-layering of the liquids is established in the sample.…”
Section: Diffusion In Meltsmentioning
confidence: 99%
“…Spatial and temporal resolution for X-ray radiography improved later, when experiments were performed at high brilliant synchrotron sources 1 or using advanced X-ray tube and detector technologies 6 .Laboratory-based X-ray sources have become a powerful tool in the last years with obvious flexibility benefits over synchrotron sources [7][8][9] . Advances in image technology, detector development and high-resolution X-ray sources combined with a wide range of furnace setups enabled the investigation of microstructure during solidification in institute laboratories and on microgravity platforms; sounding rockets or parabolic flights, for example [10][11][12][13] . Columnar and equiaxed dendritic growth 9,[14][15][16][17] , grain coarsening 18,19 and grain fragmentation 20,21 effects have been studied using thin samples with in-situ X-ray techniques under both terrestrial and microgravity conditions.…”
Section: Introductionmentioning
confidence: 99%